Congenital uterovaginal prolapse in a newborn: a case report - Suman, Bijay K.; Ram J. Singh,; Verma, Harshit; Sinha, Amit K. (International Surgery Journal, 2023)
Congenital uterovaginal prolapse in a newborn is a rare entity. It is usually associated with neural tube defects. Some cases are managed conservatively while others require more invasive management.